Measured and perceived impacts of evidence-based leadership in nursing: a mixed-methods systematic review protocol - Välimäki Maritta Anneli; Lantta Tella; Hipp Kirsi; Varpula Jaakko; Liu Gaoming; Tang Yao; Chen Wenjun; Hu Shuang; Li Xianghong (BMJ PUBLISHING GROUP, 2022)
Introduction Despite the abundance of existing literature on evidence-based nursing practice, knowledge regarding evidence-based leadership, that is, leadership supported by an evidence-based approach, is lacking. Our aim is to conduct a mixed-methods systematic review with qualitative and quantitative studies to examine how evidence is used to solve leadership problems and to describe the measured and perceived effects of evidence-based leadership on nurses and nurse leaders and their performance as well as on organisational and clinical outcomes.
Methods and analysis We will search the following databases with no year limit or language restrictions: CINAHL (EBSCO), Cochrane Library, Embase (Elsevier), PsycINFO (EBSCO), PubMed (MEDLINE), Scopus (Elsevier) and Web of Science. In addition, the databases for prospectively registered trials and other systematic reviews will be screened. We will include articles using any type of research design as long as the study includes a component of an evidence-based leadership approach. Three reviewers will independently screen all titles, abstracts and full-text articles and two reviewers will extract the data according to the appropriate checklists. The quality of each study will be appraised using specific appraisal tool fitting in study design used in each study. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) grid, PRISMA Protocols, Synthesis Without Meta-analysis and ENTREQ will guide the study process and reporting. Outcomes related to individual or group performance of nurses or nurse managers regarding leadership skills (e.g., communication skills), organisational outcomes (e.g., work environment, costs) and clinical outcomes (e.g., patient quality of life, treatment satisfaction) will be extracted and synthesised.
Ethics and dissemination This systematic review will not include empirical data, and therefore, ethics approval will not be sought. The results of the review will be disseminated in a peer-reviewed scientific journal and in a conference presentation. PROSPERO registration number CRD42021259624.